Visualization of the solid–liquid equilibria for non-flammable mixed refrigerants - Lee, Cheonkyu; Yoo, Junghyun; Lee, Jisung; Jeong, Sangkwon (Cryogenics (Guildford), 2016)
•Visualized solid–liquid equilibria (SLE) measuring apparatus has been constructed.•Measurement procedure for SLE has been confirmed by selected mixture.•Ternary MR (Ar, R14 and R218) SLE are investigated for various molar composition.•Selected ternary MR shows the freezing point depression even below 77K. Non-flammable mixed refrigerant (NF-MR) Joule Thomson (J–T) refrigerators have desirable characteristics and wide cooling temperature range compared to those of pure J–T refrigerators. However, the operating challenge due to freezing is a critical issue to realize this type of refrigerator. In this paper, the solid–liquid phase equilibria (i.e. freezing point) of the NF-MR which is composed of Argon (Ar), R14 (CF4), and R218 (C3F8), has been experimentally investigated by a visualized apparatus. The accuracy of the apparatus is experimentally verified with pure refrigerants and selected binary mixed refrigerants. Freezing points of the ternary NF-MRs have been measured with the molar compositions from 0.1 to 0.8 for each component. Each test result is simultaneously acquired by a camcorder for visual inspection and temperature measurement during a warming process. Experimental results reveal that the specific MR, with R14 molar composition higher than 0.4, can achieve remarkably low freezing temperature even below 77K. These unusual freezing point depression characteristics of the MR can be a useful information for designing a cryogenic MR J–T refrigerator to reach temperatures less than 77K.